ABAQUS–OlaFlow integrated numerical model for fluid–seabed–structure interaction. (July 2021) - Ye, Jianhong; Yu, Dawei
Abstract: In this study, a new one-way integrated numerical model for fluid–seabed–structure interaction is established by integrating the finite element software, ABAQUS, and the open-source fluid dynamics package, OlaFlow. In this new model, the generation and propagation of ocean waves as well as the seepage flow in a porous medium are controlled by OlaFlow; concurrently, the wave-induced dynamic responses of a porous seabed and marine structures are governed by ABAQUS. The reliability of this new model is validated by an analytical solution and a series of wave flume tests. The comparison results show that the new established model has high reliability and feasibility. Finally, this new integrated model is utilized for investigating the wave-induced dynamics of a composite breakwater and its seabed foundation as well as to evaluate the residual horizontal sliding displacement of the caisson of this composite breakwater under wave impact. Because this new integrated numerical model can fully utilize the advantages of both ABAQUS and OlaFlow, it is expected to have broad prospects for application in engineering practice. Highlights: An integrated numerical model for Fluid-Structures-Seabed Interaction is newly established. OlaFlow is taken as the hydrodynamics solver for generation and propagation of ocean wave. ABAQUS is taken as the solver for the wave-induced dynamics of marine structure and seabed foundation. This newly established model has been verified by analytical solution and wave flume tests. Dynamics of a composite breakwater and its foundation, the sliding of a caisson under wave loading is studied by this model.